Image processing method for a TFT LCD - Huang, Juin-Ying; Tseng, Wen-Tse; Cheng, Chien-Hsun; Wen, Shih-Sung (2010)
Image compression, decompression and motion detection methods are described. Two temporally adjacent frame images, a previous time frame and a current time frame, are compressed in round-off and averaging techniques. Next, according to the compressed data of two corresponding pixels of the two frame images, whether or not the pixel of the current time frame image is of a motion picture is detected. If the pixel is of a motion picture, the compressed pixel data of the previous time frame image is decompressed, and an overdrive process is performed on the decompressed pixel data and the original pixel data of the current time frame image to produce an overdrive output. If the pixel is not of a motion picture, an overdrive process is not performed.